Digitalisation and self-perpetuation: dynamics, drivers and temporalities of the transformation of working worlds. (7th April 2023) - Nicklich, Manuel; Pfeiffer, Sabine
Abstract : It is evident from current debates that an important new trend associated with digitalisation is the emergence of new processes, with wholly new qualities, which can be regarded as a form of 'self-perpetuation' (Verselbständigung). This article introduces the concept of self-perpetuation, the topic of this special issue, with the aim of clarifying it, making it visible in academic debates about digitalisation and examining its usefulness as an analytical tool. The contributions to this volume discuss conceptual as well as empirical aspects of this development. In addition to providing critical accounts of how self-perpetuation emerges and illustrating some of the barriers to its expansion, these articles also examine aspects of the discourses that have accompanied its historical development as well as providing glimpses into how these dynamics could be redirected in a more emancipatory fashion in the future. Taken together, these contributions demonstrate the importance of the concept of self-perpetuation for deepening our understanding of digitalisation, both as a social phenomenon and as a topic of academic research.